Representasi Perempuan Maskulin Pada Game Mobile Legends: Bang-Bang - Muhammad Wildan Wicaksono (Jurnal Ilmu Komunikasi, 2022)
Understanding gender in society often finds faults regarding one's own gender and sex. This causes masculinity in women not to be fully recognized by society. The media as a mirror of reality is supposed to show everything according to what develops in society. Games and their rapid development so that they can be connected to the internet can be categorized as media that are currently in great demand by the public. Women in games are often interpreted as sensual and weak figures. Mobile Legends: Bang-Bang as one of the most popular MOBA (Multiplayer Online Battle Arena) games shows heroes or characters that bring up masculine women through the codes they display. This study aims to determine the representation of the masculinity of female characters or heroes in the online game Mobile Legends: Bang-Bang. Using qualitative methods, this research makes semiotic analysis as its analysis technique. The semiotic analysis used is a theory by John Fiske that divides representations into three levels, namely the level of reality, the level of representation, and the level of ideology. Through this method, the heroes studied are four heroes with the most popular marksman, tank, fighter, and mage roles in the Legend tier and above. The results found from the four heroes that have been determined have a different masculinity code to highlight. These codes are seen in terms of appearance, movement, and story as the background of heroes created by game developers.